The Resurgence of Dirigent Story: Time for a Bacterial Chapter - Dabravolski, Siarhei A (Current microbiology, 2020)
For several decades, dirigent (DIR) domain-containing proteins have been assumed to be green lineage-specific, responsible for the defence response and lignan/lignin biosynthesis. Despite their high potential in terms of biotechnology and chemistry, to date there have been very few well-studied plant DIRs. However, recent achievements in sequencing technologies have allowed for discovery of DIR genes in bacteria. This prospective study suggests expansion of the focus of research to consider the existence of bacterial DIRs. It also considers the outlook for understanding DIR functioning with respect to the fields of green lineage evolution, organic synthesis, and biotechnology.
Keywords: multigenová rodina; bakteriální proteiny; lignany; rostlinné proteiny; Lignans; Bacterial Proteins; Plant Proteins; Phylogeny; lignin; proteinové domény; prospektivní studie; Lignin; fylogeneze; Prospective Studies; Bacteria; Protein Domains; Multigene Family